Pemetaan Derajat Kesadaran PHBS Berdasarkan Tingkat Pendidikan Pengunjung Tempat Wisata Delisha Resort, Konawe - mulyawati, Sufiah asri; Asmaningdiah, Mariana; Sudayasa, I Putu; Indriastuti, Diah; Bariq Kinayoh, Nuraniar; Purnamasari, Yenti; Alvionita, Dewinta Nur (Karya Kesehatan Journal of Community Engagement, 2025)
The Clean and Healthy Living Behavior (PHBS) program is a form of health promotion that aims to encourage individuals, families, groups, and communities to live in a clean and healthy environment. In public places such as tourist attractions, the implementation of PHBS is crucial to prevent the spread of disease and create a safe and comfortable environment for all visitors. This service activity aims to identify the extent to which the level of education affects the understanding and application of PHBS in a tourist site environment. The activity was carried out at Delisha Resort, Konawe Regency, Southeast Sulawesi on June 21, 2025. The activity stages include planning, implementation, and evaluation. The method used was quantitative descriptive survey with accidental sampling technique and distribution of closed questionnaires. Data were analyzed using descriptive statistics to see the distribution of education levels and the degree of awareness of PHBS. The results obtained were that the majority of visitors to tourist attractions had a very good degree of PHBS awareness. The conclusion of this service activity is that the majority of respondents who have middle and higher education backgrounds show a very good level of PHBS awareness.